Reproductive performance of Santa Inês ewes during dry and rainy seasons in eastern Amazon - Moura, A. C.B.; Teixeira, P. P.M.; Coutinho, L. N. [UNESP]; Paz, C. C.; Santos, V. J.C. [UNESP]; Soares, F. N.; Oliveira, M. E.F. [UNESP]; Vicente, W. R.R. [UNESP]; Araújo, A. A.; Rodrigues, L. F.S. (My University, 2014)
The aim of this study was to evaluate the reproductive performance of ewes during the dry and wet months in northern Brazil. The females were divided into two groups: reproduced during the dry season and lambing in the rainy season (Group A, n = 38), and the opposite with the other group (Group B, n = 55). There was no difference (P > 0.05) for expression of estrus (86.8 and 98.3%), pregnancy rate (86.8 and 90.9%), lambing (76.3 and 83.6%), abortion (9 and 7.4%), fecundity (86.8 and 96.3%), birth (103.4 and 110.8%) and prolificacy (113.7 and 115.2%) observed in groups A and B, respectively. However, there was a difference (P < 0.05) in lamb mortality (26.6% for group A and 49% for group B). Ewes from group A presented a higher average live weight at the end of the reproductive season and during the final third of pregnancy (P < 0.05).
Keywords: Amazonian climate; Lambing season; Reproductive performances; Seasonality